A 2015 global update on folic acid‐preventable spina bifida and anencephaly. Issue 7 (July 2016) - Arth, Annelise; Kancherla, Vijaya; Pachón, Helena; Zimmerman, Sarah; Johnson, Quentin; Oakley, Godfrey P.
Abstract : Background: Spina bifida and anencephaly are two major neural tube defects. They contribute substantially to perinatal, neonatal, infant, and under‐five mortality and life‐long disability. To monitor the progress toward the total prevention of folic acid‐preventable spina bifida and anencephaly (FAP SBA), we examined their global status in 2015. Methods: Based on existing data, we modeled the proportion of FAP SBA that are prevented in the year 2015 through mandatory folic acid fortification globally. We included only those countries with mandatory fortification that added at least 1.0 ppm folic acid as a fortificant to wheat and maize flour, and had complete information on coverage. Our model assumed mandatory folic acid fortification at 200 μg/day is fully protective against FAP SBA, and reduces the rate of spina bifida and anencephaly to a minimum of 0.5 per 1000 births. RESULTS: Our estimates show that, in 2015, 13.2% (35, 500 of approximately 268, 700 global cases) of FAP SBA were prevented in 58 countries through mandatory folic acid fortification of wheat and maize flour. Most countries in Europe, Africa, and Asia were not implementing mandatory fortification with folic acid. Conclusion: Knowledge that folic acid prevents spina bifida and anencephaly has existed for 25 years, yet only a small fraction of FAP SBA is being prevented worldwide. Several countries still have 5‐ to 20‐fold epidemics of FAP SBA. Implementation of mandatory fortification with folic acid offers governments a proven and rapid way to prevent FAP SBA‐associated disability and mortality, and to help achieve health‐related Sustainable Development Goals. Birth Defects Research (Part A) 106:520–529, 2016. © 2016 Wiley Periodicals, Inc.